Study the Dynamic Thiol -Disulfide Homeostasis in patients with Diabetes type I and type 2 - Zainab M.Qassam; Ekhlass M. Taha (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Diabetes is a condition in which the levels of blood glucose are abnormally high (also known as blood sugar). Diabetes mellitus is a rapidly expanding global problem with significant social, health, and economic implications.Methodology: 144 volunteers were enrolled in the current study, The volunteers were divided into four groups: the first group consist of 21 subjects with control type 1, the second group consist of 51 patients with type 1, the third group consist of 20 subjects with control type 2, and the fourth group consists of 55 subjects with patients type 2. Total thiol, Native thiol, F.B.S, and Total protein concentrations were determined using an absorbance spectrophotometer.Hba1c concentration was determined using an i-chroma.Results: The result of Total thiol, Native thiol ,Dynamic thiol-disulfide, and Total protein thiol showed a non -significant change between the fourth groups. The level of serum Hba1c and F.B.S showed a significant change among fourth groups.Conclusion: Total thiol, Native thiol, Dynamic thiol-disulfide, and Total protein do not effect by Diabetes type 1and type 2.